Mobile Health Technologies Methods and Protocols - Rasooly, Avraham (Springer, 2015)
Here we describe a low-cost mobile device that combines cell-phone and satellite communication technologies with fluid miniaturization techniques for performing all essential functions of enzyme-linked immunosorbent assay (ELISA). Disease-specific antigens are immobilized on the microfluidic surface, and disease specific antibodies are captured on the surface and visualized with silver–gold amplification. The diagnostic result is automatically determined by the device by measuring the absorbance through the silver–gold amplification in the microchannel. The results are displayed for the user and are synchronized to a remote patient record. The overall system aims to be portable, robust, low-power, and fully utilize the ability of mobile devices for bringing better health care to resource poor areas...